Analisis Yuridis Pengaruh Protokol Kyoto Terhadap Upaya Penanggulangan Pemanasan Global (Global Warming) - Yuli Anggraini; Shindy Dwianisa; Ema Septaria; M. Ilham Adepio (CV. ITTC INDONESIA, 2026)
This study examines the juridical analysis of the influence of the Kyoto Protocol on efforts to tackle global warming. Global warming is defined as an increase in the average temperature of the earth’s surface due to rising greenhouse gas emissions caused by human activities such as fossil fuel combustion, deforestation, and agricultural activities. The Kyoto Protocol, as an international legal instrument under the United Nations Framework Convention on Climate Change (UNFCCC), aims to stabilize greenhouse gas concentrations through structured and measurable regulatory mechanisms. It establishes quantitative emission reduction targets, particularly for developed countries, and introduces flexible mechanisms such as Emission Trading, Joint Implementation, and Clean Development Mechanism. However, its effectiveness remains limited due to unequal obligations between developed and developing countries, lack of binding enforcement mechanisms, and the absence of major emitting countries in its implementation. Therefore, although the Kyoto Protocol represents an important milestone in international environmental law, its impact on reducing global warming is still considered less effective.